Transitioning to artificial intelligence-based key account management: a critical assessment - Prior, Daniel D.; Marcos-Cuevas, Javier (Elsevier, 2025)
Research suggests that Artificial intelligence (AI) use for sales and marketing activities improves firm performance. Underpinning these AI applications are datasets that reflect large volumes of sales transactions and interactions with a broad range of customers. Conversely, key account relationships involve deep and focused engagements with a small number of strategically important customers at multiple levels, and this has important implications for AI data inputs and uses. Whether AI is appropriate or relevant to key account management (KAM) is currently unclear. In this paper, we critically evaluate AI applications for KAM. The paper highlights the amenability of a firm’s KAM capabilities to AI and evaluates the opportunities and challenges that AI-based KAM offers. The paper also outlines a set of moderating factors likely to affect the impact of AI on KAM and provides a conceptual model to better understand the potentially transformative effects of AI on KAM. The paper concludes with a set of theoretical and managerial implications of AI-based KAM and develops a comprehensive research agenda to contribute to the further exploration of AI-based KAM.
Keywords: 35 Commerce, Management, Tourism and Services; 3503 Business Systems In Context; 3506 Marketing; Machine Learning and Artificial Intelligence; Marketing; 3506 Marketing; 3507 Strategy, management and organisational behaviour; Key account management; Artificial intelligence; Strategic customer relationships; B2B relationships